If it's not what You are looking for type in the equation solver your own equation and let us solve it.
700=(x*9.81*4.5)/45
We move all terms to the left:
700-((x*9.81*4.5)/45)=0
We add all the numbers together, and all the variables
-((+x*9.81*4.5)/45)+700=0
We multiply all the terms by the denominator
-((+x*9.81*4.5)+700*45)=0
We calculate terms in parentheses: -((+x*9.81*4.5)+700*45), so:We get rid of parentheses
(+x*9.81*4.5)+700*45
We add all the numbers together, and all the variables
(+x*9.81*4.5)+31500
We get rid of parentheses
x*9.81*4.5+31500
Wy multiply elements
44.145x+31500
Back to the equation:
-(44.145x+31500)
-44.145x-31500=0
We move all terms containing x to the left, all other terms to the right
-44.145x=31500
x=31500/-44.145
x=-713+5.3336944745415/9.5655471289316
| -2(-5x+8)+7=-3(x-1)+7x | | r/4+56=63 | | 6p+2=2p+18 | | 4x+1=x+23 | | 2/7x=-7 | | -6(2x+8)=-8x-28 | | 5t+56=8t | | 3(z−17)−15=–15 | | 1x+3x=156 | | 3/4x-7=3x+3 | | 5y-3y+5=15 | | 18(3.4)-4=13y-38 | | 4(q+18)=12 | | 22=1/2b8 | | 6x-3(2x+4)-x=-3 | | −6(2x+8)=−8x−28 | | a+7a=8 | | m-(-5)=30 | | 3x+18=4x-2 | | -q/2+-5=-6 | | x+41-(4*x+8)=0 | | -8(6-x)=4(x+2) | | 2(d-6)=3D+8 | | -22-x/3= | | 16y×1=3(y+13) | | 28=-8x+6(x+7) | | -15=c+-5 | | 5t+9=4t-6 | | 700=x*9,81*4,5)/45 | | 15j+-2j-10=3 | | 8x+23=8(5x-5)-1 | | -22=5(u-8)-8u |